COMPARATIVE DIAGNOSIS OF Entamoeba histolytica And Giardia lamblia AMONG CHILDREN WITH DIARRHOEA AND THEIR ASSOCIATED RISK FACTORS IN SOME SELECTED HOSPITALS IN ADAMAWA STATE, NIGERIA - Kadabiyu, Ganabuto Jones (FUDMA Journal of Sciences, 2026)
A cross-sectional hospital-based study was conducted to determine the prevalence of intestinal Protozoans and other parasites among diarrheal children in some selected hospitals from November 2024 to December 2025. Stool and blood samples were obtained and examined microscopically (saline wet mount, formol-ether concentration), and serologically using Enzyme-Linked Immunosorbent Assay (ELISA), to identify the antigens of G. lamblia and E. histolytica. Questionnaires were also administered to obtain socio-demographic information and risk factors. Data collected were analysed using R-statistical software, chi-square tests, and risk factors were identified through multivariate logistic regression, with statistical significance set at p<0.05. The overall prevalence of intestinal parasite infections was 28.8%.where Specialist Hospital Yola had a higher prevalence of infection (32.5%), while the lowest was in General Hospital Numan (24.7%). Also, 5 – 12 years had a higher number of identified parasites, while the least was in under five years. The overall Sero-prevalence of the intestinal protozoan infections was 36.2%, where Entamoeba histolytica was more prevalent (22.4%) than Giardia lamblia, 69(13.8%). Sero-prevalence varied significantly by health facility (p<0.0001), E. histolytica being highest at General Hospital, Numan (30.0%), while G. lamblia was the lowest (9.0%) in Specialist Hospital, Yola. Entamoeba histolytica and Giardia lamblia are significant causes of diarrhoea among children in the study areas. The findings demonstrate that serological assays are a more sensitive diagnostic tool than conventional microscopy, revealing a higher true burden of infection. Key risk factors were identified as environmental, including unsafe water, poor sanitation, and household crowding, with school-aged children being particularly vulnerable.